2021
DOI: 10.1016/j.omto.2021.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of bispecific protein of anti-PD-1 fused with TGF-β trap enhances antitumor efficacy of CAR-T cell therapy

Abstract: Despite the remarkable success of chimeric antigen receptor-modified T (CAR-T) cell therapy for blood malignancies, the clinical efficacy of this novel therapy in solid tumor treatment is largely limited by the immunosuppressive tumor microenvironment (TME). For instance, immune checkpoints (e.g., programmed cell death protein 1 [PD-1]/programmed death ligand 1 [PD-L1]) in TME play an important role in inhibiting T cell proliferation and functions. Transforming growth factor β (TGF)-β secreted by cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…TGF-β has been shown to increase PD-1 expression on immune cells, while anti-PD-1 increases tumor cell pSMAD3 and can induce immunosuppression ( Baas et al, 2016 ; Park et al, 2016 ; Dodagatta-Marri et al, 2019 ; Wu et al, 2020 ). Thus, blockade of TGF-β signaling enhances the effects of PD-1 inhibitors or overcomes primary resistance to PD-1 blockade in silico and in vivo ( Terabe et al, 2017 ; Strauss et al, 2018 ; Chen et al, 2021 ; Siewe and Friedman, 2021 ).…”
Section: Transforming Growth Factor-β Signaling In Tumorsmentioning
confidence: 99%
“…TGF-β has been shown to increase PD-1 expression on immune cells, while anti-PD-1 increases tumor cell pSMAD3 and can induce immunosuppression ( Baas et al, 2016 ; Park et al, 2016 ; Dodagatta-Marri et al, 2019 ; Wu et al, 2020 ). Thus, blockade of TGF-β signaling enhances the effects of PD-1 inhibitors or overcomes primary resistance to PD-1 blockade in silico and in vivo ( Terabe et al, 2017 ; Strauss et al, 2018 ; Chen et al, 2021 ; Siewe and Friedman, 2021 ).…”
Section: Transforming Growth Factor-β Signaling In Tumorsmentioning
confidence: 99%
“…Studies have found the critical role of TGF-β signaling pathway in regulating cell growth, apoptosis, and differentiation, which also participates in the tumorigenesis and metastasis of HCC [69][70][71][72]. More importantly, lncRNA can regulate the progress of HCC by mediating the TGF-β signal pathway in HCC to play the role of miRNA sponge.…”
Section: Tgf-β Pathwaymentioning
confidence: 99%
“…In another study using CRL5826 positive melanoma cells, Tang and colleagues have demonstrated that knocking out the endogenous TGFβRII in CAR T cells with CRISPR/Cas9 technology could reduce the induced Treg conversion and prevent the exhaustion of CAR T cells ( 27 ). Secretion of bispecific protein of anti-PD-1 fused with TGF-β trap has also shown to enhances antitumor efficacy of CAR T cells through attenuating inhibitory T cell signaling, enhancing T cell persistence and expansion, and improving effector function and resistance to exhaustion in a prostate cancer xenograft mouse model ( 32 ). It has been well-documented that overexpression of cytokines (e.g.…”
Section: Overcoming Car T Cell Exhaustionmentioning
confidence: 99%